2015
DOI: 10.1155/2015/826358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Temperature on the Electrochemical and Optical Properties of Emeraldine Salt Doped with DBSA and Sulfuric Acid

Abstract: A comprehensive study of thermally treated polyaniline in its emeraldine salt form is presented here. It offers an understanding of the thermal stability of the polymer. Emeraldine salt was prepared by a novel emulsion polymerization pathway using dodecylbenzene sulfonic acid and sulfuric acid together as dopants. The effect of temperature and heating rate on the degradation of this emeraldine salt was studied via thermogravimetric analysis. The thermally analyzed sample was collected at various temperatures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…Both the materials displayed three different steps of weight loss in the temperature range from 25 to 800 °C. The first weight loss step from 25 to 150 °C corresponds to the evaporation of water or unreacted monomer trapped inside the PANI micropores. , No further weight loss was detected in the temperature range from 150 to 260 °C for both PANI and AuNP-PANI hybrid, illustrating that both materials are stable up to 260 °C. The TGA analysis, thus, confirmed that the incorporation of AuNPs has no influence on the thermal stability of PANI.…”
Section: Resultsmentioning
confidence: 96%
“…Both the materials displayed three different steps of weight loss in the temperature range from 25 to 800 °C. The first weight loss step from 25 to 150 °C corresponds to the evaporation of water or unreacted monomer trapped inside the PANI micropores. , No further weight loss was detected in the temperature range from 150 to 260 °C for both PANI and AuNP-PANI hybrid, illustrating that both materials are stable up to 260 °C. The TGA analysis, thus, confirmed that the incorporation of AuNPs has no influence on the thermal stability of PANI.…”
Section: Resultsmentioning
confidence: 96%
“…It is noteworthy that, in aqueous solution polymerization, relatively large temperatures (>50 °C) are usually precluded to avoid the nucleophilic attack of water [ 53 ]. On the other hand, it has been found that dry PANI backbone can withstand up to 500 °C without degradation [ 54 ]. Therefore, water-free MC polymerization of aniline should be better than that using liquid-assisted MC ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The aliphatic C–H, due to DBSA, is represented by the bands at 2825–2911 cm −1 . The HSO 4 ¯ peak at 651 cm −1 proves the presence of acidic dopants in the PANI film [38]. The FTIR analysis effectively confirms the incorporation of both DBSA and sulfuric acid moieties into the PANI backbone.…”
Section: Resultsmentioning
confidence: 99%